Influência da suplementação da ração com diferentes doses de vitamina D sobre a proteína de interação com a tiorredoxina (TXNIP) no coração e suas vias de sinalização - Santos, Priscila Portugal dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Vitamin D (VitD) deficiency has increased in recent years, becoming a public health problem. Additionally, VitD deficiency is associated with increased risk of chronic diseases developing, including cardiovascular diseases. These factors have encouraged the widespread use of this vitamin, without knowing well the alterations of different supplementation doses. Studies have shown that VitD is important for the cardiac development and function, however this vitamin can presented adverse cardiovascular effects, even at non-toxic doses. VitD acts in the target cells by binding to VitD receptor (VDR). Additionally, the thioredoxin-interacting protein (TXNIP) was identified and it expression is up-regulated by VitD. This protein acts in the regulation of signaling pathways (redox balance, apoptosis, inflammation, cell growth, metabolism energy) which can participate of the cardiac remodeling process. The aim of this study was to evaluate whether excess VitD supplementation, but in nontoxic doses, in the chow for 2 months results in change of TXNIP expression, cardiac remodeling with oxidative stress, apoptosis and alterations of inflammatory mediators and energy metabolism and whether, the supplementation increased time (for 4 months) leads to changes in cardiac structure and function. Experiment 1: 64 male rats was used and was divided into 3 groups - control (C, n = 21) received standard chow; VD3 (n = 22) and VD10 (n = 21) received 3,000 and 10,000 IU of cholecalciferol / kg of chow respectively, for 2 months; and Experiment 2: 46 male rats was used and was divided into 3 groups - control (C-4, n = 14) received standard chow; VD3-4 (n = 16) and VD10-4 (n = 14) received 3,000 and 10,000 IU of cholecalciferol / kg of chow respectively, for 4 months. After 2 and 4 months was performed echocardiography and after the animals were euthanized. The serum and the left ventricle of experiment 1 animals were used for biochemical analyzes. Statistical ...

A deficiência de vitamina D (VitD) tem aumentado nos últimos anos, tornando-se um problema de saúde pública. Adicionalmente, a deficiência de VitD está associada com o aumento do risco de desenvolvimento de várias doenças crônicas, inclusive cardiovasculares. Esses fatores têm incentivado o uso indiscriminado dessa vitamina, sem conhecer ao certo as alterações decorrentes da suplementação de diferentes doses. Estudos têm mostrado que a VitD é importante para o desenvolvimento e funcionamento cardíaco, entretanto pode ter efeito cardiovascular prejudicial, mesmo em doses consideradas não tóxicas. A VitD atua nas células alvo ligando-se ao receptor de VitD (VDR). Adicionalmente, foi identificada a Proteína de Interação com a Tiorredoxina (TXNIP) cuja expressão é regulada positivamente pela VitD. Esta proteína participa da regulação de várias vias de sinalização celular (balanço redox, apoptose, inflamação, crescimento celular, metabolismo energético) que podem ser importantes para o processo de remodelação cardíaca. O objetivo deste estudo foi avaliar se suplementação em excesso, mas em doses não tóxicas, de VitD na ração por 2 meses resulta em alteração da expressão protéica TXNIP, remodelação cardíaca com aparecimento de estresse oxidativo, apoptose e alterações de mediadores inflamatórios e metabolismo energético, e se com o aumento do tempo de suplementação de VitD (por 4 meses) ocorre alterações na morfologia e função do coração. Para isso, foram realizados o Experimento 1: utilizados 64 ratos machos, alocados em 3 grupos - Controle (C, n=21) recebeu ração padrão; VD3 (n=22) e VD10 (n=21) receberam 3.000 e 10.000 UI de colecalciferol/kg de ração respectivamente, por 2 meses; e o Experimento 2: utilizados 46 ratos machos, alocados em 3 grupos: Controle (C-4, n=14) recebeu ração padrão; VD3-4 (n=16) e VD10-4 (n=14) receberam 3.000 e 10.000 UI de colecalciferol/kg de ração...
Influence of chow supplementation with different vitamin D doses on the thioredoxin-interacting protein (TXNIP) in the heart and its signaling pathways
Keywords: Suplementos dieteticos; Stress oxidativo; Vitamina D; Remodelação ventricular; Rato como animal de laboratorio; Vitamin D